Hubungan antara Status Gizi dan Stimulasi Dini Orangtua dengan Perkembangan Bayi Usia 6-24 Bulan di Desa Kawengan Kecamatan Jepon Kabupaten Blora - Eni Oktavia Kusumaningrum (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
The treatment of a comprehensive and qualified child development organized through stimulation, early detection and intervention deviation of the growth and development of infants performed in